Why should multiple dehiscences of the otic capsule be considered before surgically treating patients with superior semicircular canal dehiscence? A radiological monocentric review and a case series - Ionescu, Eugen C.; Reynard, Pierre; Damien, Maxime; Ltaief-Boudrigua, Aicha; Hermann, Ruben; Gianoli, Gerard J.; Thai-Van, Hung (Frontiers in Neurology, 2023)
This review aims to draw attention to the multiple ipsilateral otic capsule dehiscences (OCDs), which may cause therapeutic failure in operated patients. A series of six severely disabled patients with symptoms and signs consistent with a superior semicircular canal dehiscence (SSCD) diagnosis, confirmed by a high-resolution CT scan, is presented here. Five of the patients underwent surgery, and in four of the cases, the postoperative results were poor and/or disappointing. The ethical principles underlying modern medicine encourage medical staff to learn from past experience even when the results are modest despite the accuracy of the treatment applied to a patient. Consequently, we reviewed the radiological records of symptomatic and asymptomatic patients diagnosed or referred to our center for confirmation over the past 5 years to determine the incidence of multiple OCD in this population. Multiple localizations of suspected OCD in the ipsilateral ear did not appear to be rare and were found in 29 of 157 patients (18.47%) in our retrospective review using high-resolution thin-sliced CT scans. The decision to perform surgery for a documented symptomatic superior SSCD should be made with caution only after ruling out concomitant lesser-known variants of OCD in the ipsilateral ear.